Limbal Stem Cells and their Niche: Implications for Bioengineered Tissue Constructs - Menzel-Severing, Johannes; Polisetti, N.; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2012)
Regeneration and repair of corneal epithelium rely on a reservoir of unipotent progenitor cells, which is situated within the basal epithelial layer at the corneoscleral limbus. If these cells are lost, corneal surface integrity is disturbed, which may lead to a painful loss of vision. Since the late 1990s cultivated grafts of limbal epithelium are being used therapeutically. Limbal epithelial cells are obtained from the fellow eye or from an allogeneic donor, propagated in culture on different types of carriers, and subsequently transplanted. This process entails removal of progenitor cells from their natural environment. However, surrounding cells and extracellular matrix are widely believed to provide important stimuli for stem cell maintenance and for correct differentiation. Therefore, new approaches aim at providing this so-called stem cell niche ex vivo and following transplantation. Niche factors can also drive transdifferentiation of alternative progenitor cell types towards a corneal phenotype. This permits the use of autologous cells in cases of bilateral limbal stem cell insufficiency. Several biosynthetic substrates have been devised for culture, transdifferentiation and transplantation of donor cells. This work intends to provide an overview of constructs that are currently available and to some extent clinically employed. In addition, a summary is given of novel concepts which aim at integrating putative niche factors into the stem cell carriers to replicate the stem cell niche.
EVALuna2:21097